Unleashing the Power of Green: Sustainable Success through HRM, Supply Chains, and Innovation- A Comprehensive Review of Literature - Athamneh, Mohamed Husni Al; Al-Ajlouni, Mahmoud Mohammad (Zielona Góra: Faculty of Economics and Management Press)
The burgeoning interest in sustainable company success models has experienced significant growth in recent years. Despite certain advancements in identifying this idea and promoting sustainable practices, there needs to be more understanding of the optimal organizational architecture for developing new business models or implementing sustainability-oriented adjustments in current ones.
Keywords: sustainable success; green human resource management; green supply chain performance; reen innovation technology; systematic literature review